Towards globally relevant, small-footprint dewatering solutions: Optimal conditioner dose for highly variable blackwater from non-sewered sanitation. (1st November 2022) - Shaw, Kelsey; Vogel, Michael; Andriessen, Nienke; Hardeman, Thomas; Dorea, Caetano C.; Strande, Linda
Abstract: Globally, the sanitation needs of three billion people are met by non-sewered sanitation. Small-footprint treatment technologies are needed that are appropriate for dense urban areas. Blackwater (BW) (or fecal sludge), contains more than 95% liquid, and dewatering it without conditioning requires large footprints. Chemically-enhanced dewatering with conditioners is a promising option to increase dewatering performance and reduce required footprints. However, before implementation of this solution there is a need for increased knowledge on selection and dosing of conditioners. This study evaluated bio-based and synthetic conditioners (chitosan, tannin-, and starch-based, synthetic with and without poly-acrylamide) with 14 types of BW from five countries. The supernatant after settling with jar-tests was analyzed to quantify optimal dose and dewatering performance. The reduction of total chemical oxygen demand (COD) was >55%, achieved by removal of particulate constituents with mainly soluble COD remaining in the supernatant. A reduction in particulate COD could lead to increased efficiency of soluble COD in supernatant treatment. Bio-based conditioners are as effective as synthetic conditioners, and when performance was variable, it was due to differing properties of TSS, TS, EC and pH. Optimal conditioner dose for synthetic conditioners and chitosan could be predicted using concentrations of total solids (TS) (R 2 > 0.7), whereas optimal dose for starch- and tannin-based conditioners could be predicted with electrical conductivity (EC) (R 2 > 0.8), and colloid titration (R 2 > 0.8). In addition, real-time optical TSS and EC sensors could accurately predict chitosan dose for fresh BW treated at source (R 2 = 0.97, R 2 = 0.95). This study validates that use of conditioners for dewatering with highly variable BW can be implemented with real-time measurements for optimal dose, in globally relevant implementations. Graphical abstract: Image 1 Highlights: Conditioners and settling are effective at removing pCOD from blackwater. Bio-based and synthetic conditioners are equally effective. TSS and EC can predict optimal dosage, and account for variability. Validated by blackwater samples with a wide range of characteristics. Implementation ideally based on characterization- and pilot-studies.